2021
DOI: 10.48550/arxiv.2110.14978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral States of OJ 287 blazar from Multi-wavelength Observations with $AstroSat$

K. P. Singh,
P. Kushwaha,
A. Sinha
et al.

Abstract: We present AstroSat soft X-ray, near-UV (NUV) and far-UV (FUV) observations of a blazar, OJ 287, carried out in 2017, 2018, and 2020. The simultaneous observations with NuSTAR in 2017 provide a broad-band look encompassing NUV, FUV, soft and hard X-rays. Captured in three different broadband spectral states in three observations, the X-ray spectrum is found to be the hardest during 2018, while the high-energy-end of the simultaneous optical-FUV spectrum shows a steepening that is modeled with a broken power-la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This non-thermal outburst was reported and discussed in detail by Komossa et al (2020) including the initial Swift discovery along with dedicated deep follow-up observations with XMM-Newton and NuSTAR and their modelling and interpretation, and by Komossa et al (2021d) in context with the other OJ 287 flux and spectral states of interest since 2005. [Our initial report about the detection of this outburst (ATel #13658) also triggered an additional X-ray observation (Prince et al 2021;Singh et al 2021) that still found OJ 287 in the supersoft X-ray state that characterized this outburst.] Here, we only point out that the detection of radio flaring activity independently confirms the previous conclusions about the nonthermal nature of the outburst.…”
Section: April-june Outburstmentioning
confidence: 80%
“…This non-thermal outburst was reported and discussed in detail by Komossa et al (2020) including the initial Swift discovery along with dedicated deep follow-up observations with XMM-Newton and NuSTAR and their modelling and interpretation, and by Komossa et al (2021d) in context with the other OJ 287 flux and spectral states of interest since 2005. [Our initial report about the detection of this outburst (ATel #13658) also triggered an additional X-ray observation (Prince et al 2021;Singh et al 2021) that still found OJ 287 in the supersoft X-ray state that characterized this outburst.] Here, we only point out that the detection of radio flaring activity independently confirms the previous conclusions about the nonthermal nature of the outburst.…”
Section: April-june Outburstmentioning
confidence: 80%
“…This non-thermal outburst was reported and discussed in detail by Komossa et al ( 2020 ) including the initial Swift disco v ery along with dedicated deep follo w-up observ ations with XMM-Ne wton and NuSTAR and their modelling and interpretation, and by Komossa et al ( 2021d ) in context with the other OJ 287 flux and spectral states of interest since 2005. [Our initial report about the detection of this outburst (ATel #13658) also triggered an additional X-ray observation (Prince et al 2021 ;Singh et al 2021 ) that still found OJ 287 in the supersoft X-ray state that characterized this outburst.] Here, we only point out that the detection of radio flaring activity independently confirms the previous conclusions about the nonthermal nature of the outburst.…”
Section: April-june Outburstmentioning
confidence: 82%
“…These campaigns were essential in identifying the sharp double-peaks o v er decades and in developing the binary model (e.g. Smith et al 1987 ;Sillanp ä ä et al 1988 ;Pursimo et al 2000 ;Villforth et al 2010 ;Valtonen & Sillanp ä ä 2011 ;Pihajoki, Valtonen & Ciprini 2013a ;Zola et al 2016 ;Dey et al 2018 ;Valtonen et al 2022 , and references therein), and in tracing the short-time variability characteristics with the Kepler mission (Wehrle, Carini & Wiita 2019 ). However, these important campaigns still lacked the broad-band co v erage that is necessary to distinguish between v arious dif ferent thermal and nonthermal emission processes from the jet, the accretion disc and the binary at all times.…”
Section: Introductionmentioning
confidence: 99%